2002
DOI: 10.1146/annurev.ento.47.091201.145224
|View full text |Cite
|
Sign up to set email alerts
|

Arthropod Allergens and Human Health

Abstract: Many species of arthropods are the sources of potent allergens that sensitize and induce IgE-mediated allergic reactions in humans. Most of these arthropod allergens are proteins, and the allergic response mechanism to these allergens is the same as it is for allergens from other sources such as plant pollens, molds, and foods. Aside from ingestion of crustaceans (shrimp, lobster), among arthropods, humans have the greatest contact with insects and mites, and as a result allergies to these two groups of arthro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
118
0
13

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(133 citation statements)
references
References 246 publications
(171 reference statements)
2
118
0
13
Order By: Relevance
“…Kronqvist et al (2000) reported that 12% of 440 farmers tested were sensitive to the storage mites Acarus siro, L. destructor, T. putrescentiae, and Glycyphagus domesticus. Similar sensitivities to storage mites have been reported for farmers in Scotland and USA (Arlian et al, 1997;Arlian, 2002). Important storage mite species in occupational settings are L. destructor, G. domesticus, A. siro, T. putrescentiae, Tyrophagus longior, Aleuroglyphus ovatus, Suidasia medanensis, Chortoglyphus arcuatus, and Carpoglyphus sp.…”
Section: Storage Mitessupporting
confidence: 71%
See 2 more Smart Citations
“…Kronqvist et al (2000) reported that 12% of 440 farmers tested were sensitive to the storage mites Acarus siro, L. destructor, T. putrescentiae, and Glycyphagus domesticus. Similar sensitivities to storage mites have been reported for farmers in Scotland and USA (Arlian et al, 1997;Arlian, 2002). Important storage mite species in occupational settings are L. destructor, G. domesticus, A. siro, T. putrescentiae, Tyrophagus longior, Aleuroglyphus ovatus, Suidasia medanensis, Chortoglyphus arcuatus, and Carpoglyphus sp.…”
Section: Storage Mitessupporting
confidence: 71%
“…These include some species of spider mites (e.g., the 2-spotted spider mite Tetranychus urticae and Panonychus ulmi), which are common pests in orchards, greenhouses, and gardens. These mites were recently proved to induce IgEmediated reactions (Arlian, 2001(Arlian, , 2002Solarz, 2004aSolarz, , 2006. It should come as no surprise to learn that chigger mites (larvae of Trombiculidae), ticks (Ixodida) and other species of ectoparasitic mites (Mesostigmata) of fowl, pigeons, other birds, mice, guinea pigs, and other mammals and some predaceous mites sensitize and induce allergic reactions in human (Arlian and Platts-Mills, 2001).…”
Section: Allergenic Mites As the Occupational And/or Environmental Rimentioning
confidence: 99%
See 1 more Smart Citation
“…We can conclude that overall infestation of all types of Czech stores by stored product pests was quite high provided that there is a zero pest tolerance in grain in EU countries (Bode 1996). This may have not only economical but also public health implication for the Czech Republic since many stored product pests are known as allergenic (Olsson and Hage-Hamsten 2001, Arlian 2002.…”
Section: Overall Arthropod Infestation Of the Czech Grain Storesmentioning
confidence: 99%
“…Hypersensitive humans may express a severe reaction to certain antigens, the most known being tropomyosin and chitin of crustacean arthropods. Tropomyosin is a crossreacting allergen present in insects, mites, crustaceans, mollusks, parasites and household arthropods (ARLIAN, 2002;KA HOU CHU et al, 2000;REESE et al, 1999). Chitin is a long-chain polymer of Nacetylglucosamine, a glucose derivative, being the main component of the cell walls of fungi, the exoskeletons of arthropods, such as crustaceans and insects (CAMPBELL, 1996).…”
mentioning
confidence: 99%